2008
DOI: 10.1098/rsbl.2008.0412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naturally acidified seawater on seagrass calcareous epibionts

Abstract: Surface ocean pH is likely to decrease by up to 0.4 units by 2100 due to the uptake of anthropogenic CO 2 from the atmosphere. Short-term experiments have revealed that this degree of seawater acidification can alter calcification rates in certain planktonic and benthic organisms, although the effects recorded may be shock responses and the long-term ecological effects are unknown. Here, we show the response of calcareous seagrass epibionts to elevated CO 2 partial pressure in aquaria and at a volcanic vent ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
167
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(191 citation statements)
references
References 13 publications
20
167
3
1
Order By: Relevance
“…So far, the effects of shallow venting on coastal ecosystem processes have not been sufficiently understood and evaluated (Prol-Ledesma et al, 2005) and there is even contrasting evidence as to their potential role in determining the associated biodiversity (Bianchi et al, 2011 and references therein). Shallow-water hydrothermal vents, and especially those predominated by CO 2 emissions, have lately drawn much scientific attention as natural labs for testing the effects of ocean acidification and rising sea temperatures on shallow marine ecosystems (Tarasov et al, 2005;Hall-Spencer et al, 2008;Martin et al, 2008). Apart from providing insight into upcoming climatic changes, vent-sites are important biological sources of thermophile and hyperthermophile prokaryotes that show a great potential for biotechnological applications (Dando et al, 1999).…”
Section: Vents and Seeps In Infralittoral Rock (Eunis A373)mentioning
confidence: 99%
“…So far, the effects of shallow venting on coastal ecosystem processes have not been sufficiently understood and evaluated (Prol-Ledesma et al, 2005) and there is even contrasting evidence as to their potential role in determining the associated biodiversity (Bianchi et al, 2011 and references therein). Shallow-water hydrothermal vents, and especially those predominated by CO 2 emissions, have lately drawn much scientific attention as natural labs for testing the effects of ocean acidification and rising sea temperatures on shallow marine ecosystems (Tarasov et al, 2005;Hall-Spencer et al, 2008;Martin et al, 2008). Apart from providing insight into upcoming climatic changes, vent-sites are important biological sources of thermophile and hyperthermophile prokaryotes that show a great potential for biotechnological applications (Dando et al, 1999).…”
Section: Vents and Seeps In Infralittoral Rock (Eunis A373)mentioning
confidence: 99%
“…There are indications that the processes of ocean acidification and ocean warming are closely linked and even synergistic (e.g., Rodolfo-Metalpa et al 2010). However, the effect of elevated CO 2 on marine biota is still being assessed and debated (e.g., Martin et al 2008;Nienhuis et al 2010). A number of studies using short-term experimental conditions to simulate long-term effects have lacked acclimatization time and multigenerational adaptations to the environment (as has recently been shown to occur in a species of coccolithophore, Lohbeck et al 2012), causing 'shock responses' that may not apply in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Martin et al 2008;Smith 2009;RodolfoMetalpa et al 2010;Lombardi et al 2011a, b;Loxton et al 2013). Like echinoderms, corals and pteropods, bryozoans have calcareous skeletons potentially vulnerable to dissolution (e.g., Kukliński and Taylor 2009;Smith 2009; and literature cited therein).…”
Section: Introductionmentioning
confidence: 99%
“…In particular several calcifying species exhibited a reduced calcification and growth rates in laboratory experiments under high-pCO 2 conditions. Other studies, performed in mesocosms and natural waters around volcanic vents areas, did show a clear reduction of calcareous epibionts that in turn impacted the diversity of seagrass species [5]. Conversely, it was observed that sea urchin, corals and mussels are able to survive to a decreased calcification but suffer for a reduced mechanical performance affecting in turn key biotic and abiotic interactions [6].…”
mentioning
confidence: 96%